2007
DOI: 10.1007/s10517-007-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine potentiates antipsychotic, but not cataleptogenic effect of haloperidol in rats

Abstract: Intramuscular injection of haloperidol or epinephrine in a minimum effective dose produces the maximum antipsychotic effect in rat model of schizophrenia, i.e. completely removes stereotypy, hyperlocomotion, and ataxia induced by MK-801. Haloperidol in the specified dose induces catalepsy, while epinephrine exhibits no cataleptogenic effect. Combined intramuscular injection of haloperidol and epinephrine in the threshold doses, ineffective in monotherapy, causes the maximum antipsychotic effect, but not catale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In our experiments, it was shown that stimulation of vagal afferents of the gastric mucosa by adrenomimetics (adrenaline, phenylephrine) when administered systemically at threshold doses potentiates the therapeutic effect of small doses of analgesics, antidepressants, neuroleptics, antiepileptics, and other CNS drugs to the level of therapeutic effects of therapeutic doses of the CNS drugs, but does not enhance their side effects [1,4].…”
Section: Introductionmentioning
confidence: 72%
“…In our experiments, it was shown that stimulation of vagal afferents of the gastric mucosa by adrenomimetics (adrenaline, phenylephrine) when administered systemically at threshold doses potentiates the therapeutic effect of small doses of analgesics, antidepressants, neuroleptics, antiepileptics, and other CNS drugs to the level of therapeutic effects of therapeutic doses of the CNS drugs, but does not enhance their side effects [1,4].…”
Section: Introductionmentioning
confidence: 72%